2007
DOI: 10.1016/j.yjmcc.2007.03.808
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin protects against the development of systolic dysfunction following myocardial infarction

Abstract: Background-There is an association between obesity and heart failure associated with LV dysfunction. Adiponectin is an adipocyte-derived hormone that is downregulated in obesity. Here, we examined the role of adiponectin in cardiac remodeling after myocardial infarction with loss-and gain-of-function genetic manipulations in an experimental model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
0
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(156 citation statements)
references
References 47 publications
8
142
0
6
Order By: Relevance
“…Moreover, adiponectinknockout mice develop exacerbated LV dilatation, myocyte hypertrophy, and contractile dysfunction after myocardial infarction compared with wild-type mice. 21) Therefore, adiponectin might protect the heart from LV remodeling, although it is unclear whether or not high adiponectin levels are a compensatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adiponectinknockout mice develop exacerbated LV dilatation, myocyte hypertrophy, and contractile dysfunction after myocardial infarction compared with wild-type mice. 21) Therefore, adiponectin might protect the heart from LV remodeling, although it is unclear whether or not high adiponectin levels are a compensatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have reported an inverse association between measures of adiposity and plasma levels of adiponectin as well as favorable effects of higher adiponectin levels on the risk of type 2 diabetes (15)(16)(17). In a mouse model of myocardial infarction, adiponectin-knockout mice showed exacerbation of left ventricular dilation, myocyte hypertrophy, and contractile dysfunction compared with wild-type mice, 4 weeks after ligation of left anterior descending artery (18). In contrast, administration of adiponectin to wild-type mice led to decreased left ventricular dilation and interstitial fibrosis, improved left ventricular function, and diminished apoptosis (18).…”
Section: Introductionmentioning
confidence: 93%
“…In a mouse model of myocardial infarction, adiponectin-knockout mice showed exacerbation of left ventricular dilation, myocyte hypertrophy, and contractile dysfunction compared with wild-type mice, 4 weeks after ligation of left anterior descending artery (18). In contrast, administration of adiponectin to wild-type mice led to decreased left ventricular dilation and interstitial fibrosis, improved left ventricular function, and diminished apoptosis (18). Other experiments showed that adiponectin inhibits cardiac hypertrophic response to alphaadrenergic receptor stimulation (19).…”
Section: Introductionmentioning
confidence: 98%
“…The sections were washed in distilled water and then stained with phosphomolybdic for 5 min, in aniline blue solution for 5 min, and then differentiated for 60 s. After a final wash in distilled water, the sections were dehydrated through 95% and 100% alcohol. Moreover, the heart tissue sections were digitally imaged in high-pixel resolution according to the method previously described (Shibata et al, 2007).…”
Section: Assessment Of Cardiac Fibrosis With Masson's Trichrome Stainingmentioning
confidence: 99%